2014
DOI: 10.5296/npa.v6i4.6066
|View full text |Cite
|
Sign up to set email alerts
|

RSSI Prediction in WiFi Considering Realistic Heterogeneous Restrictions

Abstract: Received Signal Strength Indicator is an indication of power level being received by a wireless device. This parameter for Wireless Fidelity has never been standardized, so any manufacturer implements it measuring as he knows better doing. This is a problem because different scenarios can be found based in several elements like: the particular Wireless Fidelity Network Interface implementation, the driver, the operating system and software monitoring implementation. This makes the utilization of the Received S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…In wireless LAN, information on the RSSI is included in the beacon packets sent by each AP at a 100 ms interval, providing a mechanism to let the terminals know the signal strength before they connect. W. Rehan et al compiled multiple insights [13], but there are several limitations to using RSSI for estimating link quality in environments with interference [14][15][16]. Subsequent studies reported that it had a specific effect as an indicator for detecting the decrease in communication link reliability at an early stage, especially when targeting AGVs [17,18].…”
Section: Related Workmentioning
confidence: 99%
“…In wireless LAN, information on the RSSI is included in the beacon packets sent by each AP at a 100 ms interval, providing a mechanism to let the terminals know the signal strength before they connect. W. Rehan et al compiled multiple insights [13], but there are several limitations to using RSSI for estimating link quality in environments with interference [14][15][16]. Subsequent studies reported that it had a specific effect as an indicator for detecting the decrease in communication link reliability at an early stage, especially when targeting AGVs [17,18].…”
Section: Related Workmentioning
confidence: 99%
“…En estos casos los costos suelen ser menores dado que la infraestructura es mucho más ligera. En esta línea es frecuente el uso de radiofrecuencia y se encuentran investigaciones que exploran WiFi (Suárez et al, 2014), ZigBee (Larranaga, Muguira, López-Garde, & Vázquez, 2010), RFID (Krukowski & Arsenijevic, 2010) y Bluetooth (Torstensson, 2016) entre otras. Todas las técnicas presentan ventajas y desventajas (Mainetti et al, 2014) que, según el entorno y las necesidades específicas del proyecto, pueden resultar de utilidad.…”
Section: Trabajos Relacionadosunclassified
“…Una sola medición, luego, es insuficiente para obtener una distancia precisa. En la experimentación 2 se modificó la aplicación para realizar más de una iteración de toma de datos y promediarlos (Suárez et al, 2014). La misma idea fue aplicada en la investigación realizada por Torstensson (2016) en donde se promediaron 3 tomas de medidas.…”
Section: Experimentaciónunclassified
“…Chen et al [41] proposed a fuzzy logic-based system to solve this problem. Suárez et al [42] proposed a linear regression model to predict Wi-Fi RSSI with considering different situations (e.g., heterogeneous devices, drivers, and operating systems). Obviously, this approach is impractical for rapidly increasing new kinds of devices.…”
Section: Design Novel Online Positioningmentioning
confidence: 99%